STEM-15. SerpinB3 DRIVES CANCER STEM CELL SURVIVAL IN GLIOBLASTOMA. (12th November 2021) - Lauko, Adam; Turaga, Soumya M; Volovetz, Josephine; Bayik, Defne; Bao, Shideng; Yu, Jennifer; Lathia, Justin
Abstract: Despite therapeutic interventions for glioblastoma (GBM), self-renewing, therapy-resistant populations of cells referred to as cancer stem cells (CSCs) drive recurrence. Previously, we identified the unique expression of junctional adhesion molecule-A (JAM-A) on CSCs and demonstrated that JAM-A is both necessary and sufficient for self-renewal and tumor growth. Moreover, we determined that JAM-A signals via Akt in GBM CSCs to sustain pluripotency transcription factor activity; however, the entire signaling network has yet to be fully elucidated. To further delineate this pathway, we immunoprecipitated JAM-A from patient-derived GBM CSCs and performed mass spectrometry to determine JAM-A binding proteins. This led to the identification of the cysteine protease inhibitor SerpinB3 as a putative JAM-A binding partner. Using in vitro CSC functional assays, we show that SerpinB3 is necessary for CSC maintenance and survival. In an in vivo orthotopic xenograft model, knockdown of SerpinB3 extended survival. Mechanistically, knockdown of SerpinB3 led to decreased expression of TGF-β, Myc, WNT, and Notch signaling, known regulators of the CSC state. Additionally, knockdown of SerpinB3 increases susceptibility to radiation therapy. SerpinB3 is essential for buffering cells against cathepsin-mediated cell death, and we found that elevated lysosomal membrane permeability after radiation leads to cathepsin release into the cytoplasm. As a result, SerpinB3 knockdown cells have a diminished capacity to inhibit cathepsin-driven cell death after radiation. The addition of the cathepsin inhibitor E64D partially rescues the SerpinB3 knockdown, however, SerpinB3 mutants that are unable to inhibit cathepsins fail to do the same. Taken together, our findings, identify a novel GBM CSC-specific survival mechanism involving a previously uninvestigated cysteine protease inhibitor, SerpinB3, and provide a potential target to increase the efficacy of standard of care GBM therapies against therapy-resistant CSCs.